Analysis of the association of bronchial asthma clinical course with ER22/23EK and TTH111I polymorphic variants in the glucocorticoid receptor gene - Kachkovska , Vladyslava (The Ukrainian Scientific Medical Youth Journal, 2023)
bronchial asthma (BA) is one of the important and urgent medical and social problems of our time due to the high incidence and prevalence, which keep increasing. This is a typical multifactorial disease determined by the influence of external factors and genetic predisposition.  The combination of these numerous factors determines the phenotypic heterogeneity of bronchial asthma. Identification of asthma phenotypes was based mainly on clinical variables; however, further identification of clinical phenotypes revealed their genetic heterogeneity. Accordingly, the determination of genetic marker data for clinical phenotypes of bronchial asthma will improve the diagnostic capabilities of preventive and evidence-based medicine in the future. The objective of the study was to determine the features of the course of early-onset and late-onset BA depending on the ER22/23EK and Tth111I polymorphisms in the glucocorticoid receptor gene and to supplement modern data on the role of genetic factors in BA onset and the severity for various phenotypes. We examined 553 BA patients and 95 apparently healthy individuals. All of them had previously signed an informed consent form. BA diagnosis, severity, and control level were determined according to the GINA recommendations-2016 and its later versions and the Decree of the Ministry of Health of Ukraine No. 868 issued on 08 October 2013.  Respiratory function was studied using Kardioplius diagnostic suite (Ukraine). The patients were divided into two clinical groups according to the BA onset: Group I included 282 patients with late-onset asthma, and Group II included 271 patients with early-onset asthma. The Bioethics Committee of the Medical Institute of Sumy State University approved the study. The ER22/23EK (rs 6189/6190) and Tth111I (rs10052957) polymorphic variants in the glucocorticoid receptor (GR) gene were determined using polymerase chain reaction-restriction fragment length polymorphism analysis. Statistical analysis of obtained results was performed using SPSS–17 program. A statistically significant difference was observed in the distribution of genotypes for the ER22/23EK and TthIIII polymorphisms in the GR gene depending on BA severity, with a higher frequency of minor alleles in both cases in patients with severe BA (χ2 = 6.09; р = 0.048 and χ2 = 15.8; р = 0.001, respectively). The relative risk of severe BA did not depend on the ER22/23EK polymorphism in the GR gene; however, it was 3.63 times higher in the carriers of the TT genotype for the Tth111I polymorphism vs. carriers of the major allele homozygotes. The risk of severe disease in early-onset and late-onset BA depended on the Tth111I polymorphism in the GR gene; in the recessive model, it increased by 3.7 times for early-onset asthma and by 3.5 times – for late-onset asthma. Analysis of ER22/23EK (rs 6189/6190) and Tth111I (rs10052957) polymorphic variants in the GR gene demonstrated their possible correlation not only with the increased risk of BA, but also with certain phenotypes and severity of the disease.